Competency on Breast Feeding among Mothers of High Risk Babies and Practice of Nurses in Assisting the Mothers with a View to Develop A Protocol (Indian Journal of Public Health Research & Development, 2020)
Introduction: The mother of a high risk neonate is confronted with numerous parenting challenges, notthe least of which is the decision about how to nourish her vulnerable newborn. Successful breastfeedingdepends on overcoming obstacles posed by neonate’s condition, maternal health, and intensive care unitenvironment.Objective: to assess the competency on breastfeeding among mothers of high risk babies and practice ofnurses in assisting the mothers in selected Intensive Care Unit, AIMS, Kochi, with a view to develop anursing care protocol.Methodology: The descriptive research design was adopted and non-probability convenience samplingtechnique was used to collect data from 40 mothers by using structured questionnaire and observationalchecklists to assess the practice of mothers and staff nurses in NICU.Results: The study reveals that 22 (55%) mothers were having average knowledge and most of the mothers23 (57.5%) had poor practice regarding the breastfeeding of the high risk neonate in NICU. Most of the staffnurses (50%) had average level of practice while assisting the mothers during breastfeeding in NICU. Thereis significant association between knowledge and demographic variables like education of the mother, orderof pregnancy and source of knowledge.Conclusion: The nursing protocol was implemented and established a comprehensive improvement in theknowledge, care, support and management. Thus, the health care professional ultimately work towardsproviding a positive impact on the lives of high risk neonate.
Keywords: Breastfeeding, High risk neonates, Mother.